2021
DOI: 10.1097/md.0000000000027141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corneal endothelial cell changes after phacoemulsification between type 2 diabetic and nondiabetic patients

Abstract: The aim of this study is to compare the endothelial cell density (ECD) and morphology between diabetic mellitus (DM) and nondiabetic patients at 1 year after phacoemulsification in operated eyes and nonoperated eyes. Evaluation was performed in 28 patients (56 eyes) with type 2 diabetes and 37 patients (74 eyes) without diabetes who underwent 1-year interval cataract surgery. Using a noncontact specular microscope and Scheimpflug rotating camera, corneal parameters were analyzed before and 1 year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The graph of both ECD and hexagonality has nearly the same curve; anyway, the percentage of hexagonality has the decreased rate as 1.08%/year which is resemblance to the rate of ECD reduction. Those data affirm that the different endothelial qualifications such as ECD and hexagonality reach the evaluation dimensions consistency which coincide with Joo et al's publications [23]. The size and hexagon of endothelial cell area can be the unique property for the human develop-ment [24].…”
Section: The Characteristic Of 4-30 Years Chinese's Endothelialsupporting
confidence: 87%
“…The graph of both ECD and hexagonality has nearly the same curve; anyway, the percentage of hexagonality has the decreased rate as 1.08%/year which is resemblance to the rate of ECD reduction. Those data affirm that the different endothelial qualifications such as ECD and hexagonality reach the evaluation dimensions consistency which coincide with Joo et al's publications [23]. The size and hexagon of endothelial cell area can be the unique property for the human develop-ment [24].…”
Section: The Characteristic Of 4-30 Years Chinese's Endothelialsupporting
confidence: 87%
“…The HEX percentage significantly declined in the diabetic individuals, showing that type 2 diabetes slows the rate of endothelial cell repair, while the CV and the CCT did not differ among the groups three months after surgery in contrast to the current research. Also, Joo JH, et al [20] found that one year after phacoemulsification, diabetes individuals lost more corneal endothelial cells than non-diabetic patients, but there were no statistically significant differences. The ECD In diabetic group and the control group both decreased significantly over the preoperative ECD in the operated eye, but neither group's ECD decreased significantly over the course of a year in the other non-operated eye.…”
Section: Discussionmentioning
confidence: 98%
“…The percentage of endothelial cell loss (ECL%) in patients with DM was reported to be significantly higher than that in the control group after phacoemulsification [ 41 , 42 ], and the damage was not restored to the preoperative state at 6 months postoperatively [ 14 ]. Joo et al [ 43 ] found that the ECL in patients with DM was higher than that in non-DM patients 1 year after phacoemulsification, although not statistically significant. Furthermore, the duration of DM may affect postoperative ECD loss, with more ECD loss occurring when the duration is ≥ 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The HCP returned to its preoperative state 6 months postoperatively [ 14 ]. No significant change was found in the CV and HCP in either group at 1 year postoperatively [ 43 ].…”
Section: Discussionmentioning
confidence: 99%